Transnational Muslims in American Society - Alexandra Jerome (International Institute of Islamic Thought, 2008)
In post-9/11 America, the necessity for a comprehensive study of transnational Muslim communities, as well as their identities and dynamics within American society, is filled by Aminah Beverly McCloud’s Transnational Muslims in American Society. This comprehensive study examines a crosssection of Muslim communities in diaspora and exile, from the Palestinians to the Iranians to the very small community ofMuslim Chinese. The author’s examination, which loosely relies on notoriously vague immigration records, first-person interviews, and clever anecdotes, is also coupled with a general history and overviewof Islamand the individual communities. The brief histories of each community and its ethnic, cultural, and Islamic idiosyncrasies, placed at the beginning of each chapter, are particularly helpful. In addition, her nuanced analyses ofwomen’s positions in the contexts of their own communities provides an important depth to the study ...